2015
DOI: 10.1016/j.jconhyd.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of biofilms on the mobility of bare and capped zinc oxide nanoparticles in saturated sand and glass beads

Abstract: Biofilms are a common constituent of the subsurface and are known to influence contaminant transport; however only a few studies to date have addressed microbial controls on nanoparticle mobility in porous media. The impact of a 3-day Pantoea agglomerans biofilm on the mobility of zinc oxide (ZnO) nanoparticles was studied in column experiments containing sand and glass beads at near-neutral pH and constant ionic strength. Bare ZnO nanoparticles (bZnO-NPs) and ZnO nanoparticles capped with tri-aminopropyltriet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Besides significant chemical effects, Pantoea agglomerans may prevent penetration of harmful industrial contaminants into deeper parts of soil on a physicochemical basis. Kurlanda-Witek et al [166] have experimentally demonstrated that even a thin layer of a biofilm formed by P. agglomerans can hinder the migration of zinc oxide nanoparticles downwards porous media. The authors postulated that such biofilms could be used as a potential remediation strategy against the migration of nanoparticle contaminants in heterogeneous aquifers [166].…”
Section: Prevention Of Penetration Of Toxic Contaminants Into Soilmentioning
confidence: 99%
“…Besides significant chemical effects, Pantoea agglomerans may prevent penetration of harmful industrial contaminants into deeper parts of soil on a physicochemical basis. Kurlanda-Witek et al [166] have experimentally demonstrated that even a thin layer of a biofilm formed by P. agglomerans can hinder the migration of zinc oxide nanoparticles downwards porous media. The authors postulated that such biofilms could be used as a potential remediation strategy against the migration of nanoparticle contaminants in heterogeneous aquifers [166].…”
Section: Prevention Of Penetration Of Toxic Contaminants Into Soilmentioning
confidence: 99%
“…It was also observed in column transport experiments where retention of ENPs increases in presence of these microbial structures: latex NPs and CdSe/ZnS quantum dots (QDs) (Tripathi et al, 2012), zerovalent Fe-NPs (Lerner et al, 2012;Crampon et al, 2018), nano-ZnO (Jiang et al, 2013), biogenic nano-Se (Wang et al, 2019), nano-Ag (Xiao and Wiesner, 2013). This increased retention in column experiments is generally explained by changes in roughness, surface charge and hydrophobicity at the surface of aquifer grains (Donlan, 2002;Kurlanda-Witek et al, 2015) in addition to the intrinsic accumulation properties of these microbial structures.…”
Section: Biofilms: Important Environmental Accumulatorsmentioning
confidence: 74%
“…60 Spherical and granular microplastics are more likely to migrate to deeper soils. 61 Leaching also has a significant positive effect on the vertical motion of microplastics. Soil organic carbon (SOC) and clay have important effects on the adsorption and migration of polystyrene microplastics.…”
Section: Migration and Transformation Of Microplastics In Soilmentioning
confidence: 99%
“…O’Connor et al reported the mobility of five different MPs, which consisted of polyethylene (PE) and polypropylene (PP) particles of various sizes and densities, and observed that small-sized PE MPs (21 μm) had the greatest movement potential . Spherical and granular microplastics are more likely to migrate to deeper soils . Leaching also has a significant positive effect on the vertical motion of microplastics.…”
Section: Migration and Transformation Of Microplastics In Soilmentioning
confidence: 99%